Variable speed drive fundamentals - Phipps, Clarence A., 1922- (Fairmont Press, 1999)
Annotation Written in straightforward "user" language, this book provides an authoritative, yet practical guide for the engineer or technician involved in specifying, applying, maintaining or operating variable frequency drives (VFDs). A comprehensive overview of starting controls and their application to various types of induction motors provides a valuable assessment of the advantages and disadvantages of each type of control. You'll find a helpful discussion of some of the latest electronic "smart" motor controllers, as well as a section covering the attributes and capabilities of the "wound-rotor motor," including how to configure a basic control system for it. A basis is given to compare motor torque and operating characteristics using "starters." The presentation provides a detailed evaluation of the most common versions of variable frequency drives. Current trends in addressing harmonic problems created by VFDs are discussed, along with use of new IGBT technology. Other topics include sizing and applying of VFDs, controlling enclosure heat, and energy saving opportunities.
Includes index.
Keywords: Variable speed drives.; elektronické knihy; electronic books